Simulation of BRKSS Architecture for Data Warehouse Employing Shared Nothing Clustering - Bikramjit Pal; Mallika De (International Journal of Engineering and Management Research, 2019)
The BRKSS Architecture is based upon shared nothing clustering that can scale-up to a large number of computers, increase their speed and maintain the work load. The architecture comprises of a console along with a CPU that also acts as a buffer and stores information based on the processing of transactions, when a batch enters into the system. This console is connected to a switch (p-ports) which is again connected to the c-number of clusters through their respective hubs. The architecture can be used for personal databases and for online databases like cloud through router. This architecture uses the concept of load balancing by moving the transaction among various nodes within the clusters so that the overhead of a particular node can be minimised. In this paper we have simulated the working of BRKSS architecture using JDK 1.7 with Net beans 8.0.2. We compared the result of performance parameters sch as turnaround time, throughput and waiting time with existing hierarchical clustering model.